The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2174/1875038901003010027
|View full text |Cite
|
Sign up to set email alerts
|

Application of Electrochemical Methods for Analysis of Fluoroquinolones Antibacterial Agents and Fluoroquinolones-DNA Interactions

Abstract: This mini review describes the results regarding the voltammetric determination of micromolar, submicromolar and nanomolar concentrations of various fluoroquinolones antibacterial agents using both traditional hanging mercury drop electrode, carbon paste electrode, glassy carbon paste electrode and chemically modified electrodes. We concentrate on the interaction of quinolones with DNA in solution and at electrode surface in the context of the general development in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…The literature survey revealed that there are several analytical methods have been reported for LVF assay include spectroscopy [13][14][15][16][17][18] , LC [19][20][21][22][23][24][25][26] , CE 27 , and electrochemistry [28][29][30][31][32][33][34][35][36][37] . Electrochemical methods have been proven to be sensitive and reliable for the assay of various drugs in biological fluids and pharmaceutical formulations 38 . Ion selective potentiometric sensors have a variety of applications due to its excellent advantages like high sensitivity, high selectivity, and being quick and easy to use 39 .…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey revealed that there are several analytical methods have been reported for LVF assay include spectroscopy [13][14][15][16][17][18] , LC [19][20][21][22][23][24][25][26] , CE 27 , and electrochemistry [28][29][30][31][32][33][34][35][36][37] . Electrochemical methods have been proven to be sensitive and reliable for the assay of various drugs in biological fluids and pharmaceutical formulations 38 . Ion selective potentiometric sensors have a variety of applications due to its excellent advantages like high sensitivity, high selectivity, and being quick and easy to use 39 .…”
Section: Introductionmentioning
confidence: 99%